KEY FACTORS IN THE MANAGEMENT OF HORIZONTALLY INTEGRATED STRUCTURE OF MEDICAL SERVICES COMPANIES - Ivan Doshkov; Mariela Deliverska (Peytchinski Publishing, 2017)
Marketing management in the sphere of health services is an activity, which has to do with evaluation of the potential (economic, demographic, morbidity etc.) in a given geographical region and with outlining the framework of a competitive and profitable business. For the provision of effective management, a thorough economic analysis of the healthcare activities is necessary. With view to optimization of the results, economic evaluation at different levels needs to be made, including systematic consideration of the factors, which influence the decision for directing the resources to a given alternative use at the expense of other use. The management of a healthcare enterprise is successful, only if the management of its individual units is successful and if they work in line with one another for the achievement of the common targets of the organization.